‘We Are Gunslinging Girls:’ Gender and Place in Playground Clapping Games - Casals, Albert; Riera, Joanna (Atlantis, 2015)
This article presents a qualitative study of clapping games in the playground, a space directly conditioned by its historical and socio-cultural context. Based on qualitative interviews and observations with adults and children in Catalonia, Spain, we argue that the repressive Francisco Franco dictatorship (1939-1975) and the emergence of Spanish feminist and other critical movements in the late 1960s have shaped the nature of clapping games in school playgrounds. Through a close analysis of their lyrics, we defend the idea that the study of clapping games is important for understanding the gendered geographies and culturally-specific moments of girlhood in Catalonia, and highlight the role of playgrounds as spaces where girls negotiate their roles and identities.